Bee Well: a positive psychological impact of a pro-environmental intervention on beekeepers’ and their families’ wellbeing - Burke, Jolanta; Corrigan, Sean (Frontiers in Psychology, 2024)
Bees are excellent pollinators and serve an essential environmental purpose. However, little is known about the wellbeing impact of bees on humans. This research addressed the knowledge gap concerning the impact of beekeeping on the wellbeing of beekeepers and their families, focusing on the often-overlooked psychological, emotional, and social dimensions. Thirty farmers in Ireland participating in the Let it Bee project, aimed at promoting biodiversity and water source protection, were provided with bee hives. Twelve participants were interviewed to explore the effects of beekeeping on their wellbeing. Thematic Analysis was employed to analyze the data, revealing five central themes. (1) The centrality of pride in accomplishing environmental and community objectives in the farmers’ beekeeping activities; (2) the evolving sense of togetherness with nature, family, and community throughout the project; (3) a profound sense of contributing significantly to the greater good; (4) the recognized value of beekeeping for beekeepers’ psychological growth, flow, and relaxation; and (5) the opportunity for beekeepers to leverage their character strengths. The implications of these findings are discussed within the framework of their impact on environmental conservation, healthcare policymaking, and implications for research and practice.